Effect of Compound Muscle Action Potential After Peripheral Nerve Stimulation Normalization on Anesthetic Fade of Intraoperative Transcranial Motor-Evoked Potential. Issue 4 (July 2021) - Tanaka, Satoshi; Watanabe, Tomoko; Takanashi, Junko; Oka, Hidehiro; Hashimoto, Ryo; Akimoto, Jiro
Abstract : Purpose: Anesthetic fade refers to the time-dependent decrease in the amplitude of the intraoperative motor-evoked potential. It is thought to be caused by the accumulation of propofol. The authors examined whether normalization by the compound muscle action potential (CMAP) after peripheral nerve stimulation could compensate for anesthetic fade. Methods: In 1, 842 muscles in 578 surgeries, which did not exhibit a motor-neurologic change after the operation, the motor-evoked potential amplitude was normalized by the CMAP amplitude after peripheral nerve stimulation, and the CMAP amplitude and operation times were analyzed. Results: The amplitudes of both motor-evoked potential and CMAP increased over time after peripheral nerve stimulation because of the disappearance of muscle-relaxant action. Especially, after peripheral nerve stimulation, CMAP significantly increased from the beginning to the end of the operation. Anesthetic fade in transcranial motor-evoked potential monitoring seemed to occur at more than 235 minutes of surgery based on the results of a receiver operating characteristic analysis of the operation time and relative amplitudes. Although the mean amplitude without CMAP normalization at more than 235 minutes was significantly lower than that at less than 235 minutes, the mean amplitude with normalization by CMAP after peripheral nerve stimulation at more than 235 minutes was not significantly different from that at less than 235 minutes. Conclusions: Compound muscle action potential after peripheral nerve stimulation normalization was able to avoid the effect of anesthetic fade. Anesthetic fade was seemed to be caused by a decrease in synaptic transmission at the neuromuscular junction because of propofol accumulation by this result.